Pulmonary Artery Catheter Use in Off-Pump Coronary Artery Bypass Grafting (Opcabg): Clinical Efficacy and Outcome Implications - Kaur, Gagandeep; Ojha, Shailesh; Thirunavukkarasu, Barathan; Dhawan, Akshay (Journal of Neonatal Surgery, 2025)
The pulmonary artery catheter (PAC) has been a cornerstone of peri-operative haemodynamic monitoring since Swan and Ganz first described flow-directed catheterisation of the right heart in 1970 . Over the past three decades its routine use in general intensive care has waned, driven by landmark trials that failed to show survival benefit and by the emergence of less-invasive technologies. Nevertheless, in cardiac surgery and particularly in off-pump coronary artery bypass grafting (OPCABG), where the heart is manipulated on a beating circulationhaemodynamic perturbations remain profound and rapid-onset. Optimising preload, afterload and contractility in this context is intuitively attractive, yet the incremental value of a PAC over alternative monitors remains controversial. This narrative review synthesises historical and contemporary evidence, explores physiologic rationale, summarises clinical outcome data, evaluates cost-effectiveness, outlines complication profiles, and discusses guideline recommendations for PAC use in OPCABG. A systematic search of PubMed, Embase, Scopus and major society websites up to March 2025 identified 142 relevant publications, of which 78 comprising 12 randomised or quasi-randomised trials, 5 large propensity-matched cohort studies, 3 registry analyses and 58 mechanistic or observational studies—inform this review. The preponderance of recent high-quality data suggests that selective PAC deployment in haemodynamically complex OPCABG (e.g., severe pulmonary hypertension, right heart dysfunction, poor ventricular compliance, anticipated multi-vessel posterior wall grafting) is associated with improved renal and pulmonary outcomes without a clear mortality signal, albeit at the cost of low-frequency but potentially catastrophic mechanical complications. Integrating PAC-derived metrics with trans-oesophageal echocardiography (TEE), near-infra-red spectroscopy (NIRS) and advanced arterial pressure waveform analysis appears to confer the greatest benefit. Future research should focus on hybrid optical-pressure catheters, continuous right-ventricular ejection fraction sensors and machine-learning decision support